Serum uric acid to creatinine ratio as a predictor of insulin resistance, β cell function, and metabolic syndrome in normal Korean adults: a cross-sectional study - Misuk Oh; Soo Hyun Cho (BMC Endocrine Disorders)
Abstract Background This study aimed to determine the relations between serum uric acid to creatinine ratio(SUA/Cr) and insulin resistance, pancreatic β cell function, and outbreak of metabolic syndrome (MetS) in normal Korean participants. Materials and methods This study included 14,984 participants without diabetes mellitus or gout who participated in the 2019–2021 Korea National Health and Nutrition Examination Survey. To evaluate insulin resistance and β cell function, the homeostasis model assessment (HOMA) was used. Insulin resistance was suggested by HOMA-IR, and β cell function was presented as HOMA-β. Multivariate logistic linear regression analysis was used to identify the factors affecting HOMA-IR, HOMA-β, and MetS. Cut-off values of SUA/Cr to predict insulin resistance, β cell dysfunction, and MetS risk were also been suggested. Results Consequent to dividing SUA/Cr into tertiles, the higher the SUA/Cr, the higher the HOMA-IR and dysfunction of β cell, and the rate of MetS increased (p < 0.05). SUA/Cr was associated with insulin resistance, β cell function, and existence of MetS (adjusted odds ratio [OR]; 1.231 [95% confidence interval [CI]; 1.204–1.259], 1.033 [1.011–1.057], and 1.065 [1.026–1.106], respectively). In addition, the group with the clinical significance was the 3rd tertile. In this group, insulin resistance, β cell dysfunction, and MetS risk could be predicted when SUA/Cr value was 8.2716, 8.8710, and 7.9762, respectively. Based on the total number of people, meaningful SUA/Cr values were 7.0175, 6.7925, and 6.9369. Conclusions The SUA/Cr may be a useful marker for predicting the insulin resistance, β cell function and incidence of MetS in normal Korean participants.